Essential Inclusive Education-Related Outcomes for Alberta Preservice Teachers - Loreman, Tim (Alberta Journal of Educational Research, 2010)
This article examines the knowledge, skills, and attributes (KSAs) that Alberta preservice teachers need to develop over the course of their teacher preparation programs in order to work effectively in inclusive classrooms. Inclusive classrooms are those where all students regardless of diversity learn in the same contexts. These KSAs are presented as program outcomes and are identified in relation to their prominence in the literature on inclusion and their alignment with Alberta education policy and teacher interim certification requirements. They were then reviewed by a focus group of representatives from teacher preparation institutions in Alberta and Canada. The author suggests that teacher preparation institutions in Alberta must ensure that these outcomes are addressed at multiple points throughout their teacher preparation programs.